Upaya Peningkatan Kemampuan Literasi Digital Bagi Tenaga Perpustakaan Sekolah dan Guru di Wilayah Jakarta Pusat Melalui Pelatihan Literasi Informasi - Indah Kurnianingsih; Rosini Rosini; Nita Ismayati (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2017)
The enhancing of information technology and internet, resulting in digital information resources are very abundant. Now days, the students in Indonesia as a digital native has a high dependence on the internet. The lack of information literacy skill among learners has a bad impacts. One of them is many plagiarism of copyrighted work happened in the school academic . This becomes a challenge for teachers and school librarian to solve this problem. The purpose of this information literacy training program is to provide skills for teachers and school librarian in order to teach students to be able to recognize what kinds of information are needed, electronic information sources, digital information sources search strategies, and information evaluation. Thus, the engagement community entitled